2017
DOI: 10.1021/acs.est.7b02014
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Ascaris Eggs in Human Fecal Material Through In Situ Production of Carboxylic Acids

Abstract: Discovering new ways to inactivate pathogens in human waste is critical for the improvement of worldwide access to sanitation and for the reduction of the environmental impact of conventional waste treatment processes. Here, we utilized the carboxylate platform and chain elongation to produce n-butyric acid and n-caproic acid via the anaerobic fermentation of human fecal material. Then, we inactivated Ascaris eggs through exposure to these carboxylic acids. Using batch experiments with human fecal material as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
3
29
1
Order By: Relevance
“…Beyond n-butyric acid (C4), the undissociated carboxylic acid is no longer miscible, with the maximum solubility concentration in water decreasing by more than 10-fold for each elongation step (Table S1). Many studies have also shown a trend of increasing toxicity with carbon-chain length [13][14][15][16][17] ; however, some Gram-negative bacteria show resistance to MCCAs longer than C8. 13,14 As a result, the MCCAs could be continuously extracted with a membrane-based liquid-liquid extraction (i.e., pertraction) or other extraction systems to prevent product inhibition.…”
Section: Context and Scalementioning
confidence: 99%
“…Beyond n-butyric acid (C4), the undissociated carboxylic acid is no longer miscible, with the maximum solubility concentration in water decreasing by more than 10-fold for each elongation step (Table S1). Many studies have also shown a trend of increasing toxicity with carbon-chain length [13][14][15][16][17] ; however, some Gram-negative bacteria show resistance to MCCAs longer than C8. 13,14 As a result, the MCCAs could be continuously extracted with a membrane-based liquid-liquid extraction (i.e., pertraction) or other extraction systems to prevent product inhibition.…”
Section: Context and Scalementioning
confidence: 99%
“…One method under investigation uses anaerobic fermentation of human fecal material (HFM) to produce carboxylic acids (Harroff et al, 2017). Complex organic molecules are first broken down to short-chain carboxylic acids (e.g., acetic acid, propionic acid, and n-butyric acid) through hydrolysis and primary fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, molecules with even-numbered hydrocarbon chains are more common than those with odd-numbered chains, but both are produced. Previous work has shown that HFM can be used as substrate to produce up to 257 mM n-butyric acid, 11.3 mM n-valeric acid, and 27.1 mM n-caproic acid (Harroff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations